Perspectives on the role of National Fatwa Committee in handling food issues in Malaysia based on Maqasid Syariah - Awang, M.D.; Yahaya, M.M.; Sulaiman, M.; Ismail, K.; Baharum, N.B.; Abdullah, A.A. (Rynnye Lyan Resources, 2023)
The National Fatwa Committee (NFC) is a body responsible for issuing fatwa in Malaysia. It has an important role in determining a fatwa on a certain issue whether permissible or not. Among the popular issue in the current community are food issues. These include the issues of swine DNA in food, consuming fish oil and other several significant food issues. This study aimed to study fatwa production of these issues by NFC. This fatwa tried to use the Maqasid Syariah and its understanding through scientific views and understanding. It was also noted that before a fatwa is produced, it will have to go through several processes before it is distributed to the public. This study used the qualitative method, by referring to files or documents, journals, and interviews. The study also found that most of the fatwa was made by referring to al-Shafie school of teaching and several methods in deriving laws based on illah (reason) as relevant fiqh methodology to understand the Maqasid Syariah through a scientific study. Therefore, the fatwa has been made by referring to not only the fiqh but also the science information obtained through the lab work.